Contribuição ao projeto e execução de lajes lisas nervuradas pré-fabricadas com vigotas treliçadas - Avilla Junior, Jovair (2010)
The big surge in use of systems for flat slabs gave up the search for freedom in the definition and organization of architectural interior spaces in buildings. The design and construction of buildings on flat slabs, which allow great mobility in defining the internal space of the building and reducing its height. The slabs with prefabricated trussed beams using forms lost in blocks of expanded polystyrene (EPS) or removable forms, brought new perspectives to the design of flat slabs, allowing greater spans with low deadweight. The precast elements are lightweight, easy handling, transport and assembly, and require the use of molds and special equipment and requires little bracing. Computer programs have emerged in recent years provide more refined calculations that predict the behavior of the structure in service with greater precision. This way the designers have increased security in systems design less common as flat slabs ribbed, without internal beams, capitals and even edge beams. In Brazil the predominant culture in the design and implementation of flat slabs is given by the system option molded on site. The objectives of this study are: to seek answers to the prevailing cultural behavior, and to compare their advantages and disadvantages when compared with cast on site, presenting the normative regulations and simplified calculation method according to ABNT NBR 6118:2003, provide subsidies for the project and implementation of flat slabs with ribbed prefabricated trussed beams, provide a calculation method for the infinitely rigid diaphragm; present a real case study as a comparison of costs.